2021
DOI: 10.1186/s12903-021-01974-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concha bullosa and nasal septal deviation on palatal dimensions: a cone beam computed tomography study

Abstract: Introduction Nasal septal deviation (NSD) and concha bullosa (CB) are associated with airway obstruction in mouth breathers. Mouth breathing is associated with alterations in maxillary growth and palatal architecture. The aim of our study was to determine the effect of the presence of CB and NSD on the dimensions of the hard palate using cone-beam computed tomography (CBCT). Materials and methods A retrospective study was conducted using CBCT scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The criteria for determining ITH was based on the maximal width of inferior turbinate in the coronal CBCT section. A width of more than 10 mm was considered as ITH, based on the findings of published CT and CBCT studies ( Jha, Ghimire & Shrestha, 2020 ; Shetty et al, 2021 ). Based on the maximal width of the right and left turbinates the scans were further subdivided as unilateral or bilateral ITH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for determining ITH was based on the maximal width of inferior turbinate in the coronal CBCT section. A width of more than 10 mm was considered as ITH, based on the findings of published CT and CBCT studies ( Jha, Ghimire & Shrestha, 2020 ; Shetty et al, 2021 ). Based on the maximal width of the right and left turbinates the scans were further subdivided as unilateral or bilateral ITH.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from lower radiation dose CBCT has higher image resolution, lower cost and provides thinner image slices compared to CT. In our previous work we have studied the association between NSD and inferior turbinate hypertrophy (ITH) using CBCT ( Shetty et al, 2021 ). We found that the width of the inferior nasal turbinates had an association with the degree of nasal septal deviation.…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical variants of the nasal turbinates are important in the pathogenesis of the inflammatory processes of the paranasal sinuses, such as for the etiology of sinusitis associated with the middle turbinate (4,5). A significant correlation between the palatal dimensions, the presence of the concha bullosa and the deviation of the nasal septum that can contribute to the establishment of the skeletal malocclusion is also mentioned (6). In addition, the presence of the concha bullosa and deviation of the nasal septum would be related to compensatory hypertrophy of the contralateral turbinate (7).…”
mentioning
confidence: 94%
“…Since its complete spectrum cannot be covered within the undergraduate curriculum, previous studies have stated the importance of solid theoretical foundation and suitable clinical experience before the clinical internship or rotation [8,9]. Multiple teaching approaches have been introduced into the undergraduate setting of implant dentistry education, including implant planning software, virtual reality training, and 3D modelling [10][11][12]. Nevertheless, current teaching modes only focused on the preclinical training inside the laboratory, and barriers in implant dentistry education still exist, such as lack of clinical training, and divorce of theory and clinical practice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since its complete spectrum cannot be covered within the undergraduate curriculum, previous studies have stated the importance of solid theoretical foundation and suitable clinical experience before the clinical internship or rotation [8,9]. Multiple teaching approaches have been introduced into the undergraduate setting of implant dentistry education, including implant planning software, virtual reality training, and 3D modelling [10][11][12].…”
Section: Introductionmentioning
confidence: 99%